Novel panel-core connection process and impact behaviors of CF/PEEK thermoplastic composite sandwich structures with truss cores. (1st November 2020) - Hu, Jiqiang; Liu, Ankang; Zhu, Shaowei; Zhang, Hanqi; Wang, Bing; Zheng, Huayong; Zhou, Zhengong
Highlights: Based on the characteristics of CF/PEEK, a new manufacturing process is proposed for CF/PEEK sandwich structure. A novel in-suit hot-pressing connection technology is proposed for the connection between the panel and the truss core. The FE model provide a way for designers to study the low-velocity impact response of FRP sandwich structures. Abstract: The composite sandwich structures, as a representative of lightweight and high-strength structures, exhibit extraordinary engineering application potential. However, the weak connection between panel and core limits their application. This paper focuses on investigating the panel-core connection and impact properties of the carbon fiber reinforced polyether ether ketone (CF/PEEK) sandwich structure with truss core. An in-suit hot-pressing connection technology distinguishing from traditional brazing (for metal materials) and bonding (for thermosetting composites) methods is proposed for connecting panels and truss cores. The low velocity impact test were carried out to investigate the impact response and failure modes of the CF/PEEK sandwich structures. The finite element (FE) model is established to predict the structural response under low velocity impact loading. The impact response of the structure is analyzed using experimental and simulation results, which are affected by relative density of core, impact energy and impact site. Besides, parametric analyses on impactor diameter and unit cell number was carried out. This work provides guidance for studying the impact performance of composite sandwich structures.